The effects of institutions on emerging market firms’ international assignment location decisions - Koleša, Iris (Economic and business review, 2022)
We investigate international assignment (IA) location decisions of emerging market firms as determined by the institutional contexts of their home and host countries. Using an institutional perspective, assignment patterns of the entire firm population in Slovenia to either other emerging or developed host countries in Europe are analysed. The findings show that both institutional quality and distance influence expatriation flows in firms from a low quality institutional context. These firms expatriate more to markets with high quality institutions and choose host countries with higher rather than smaller institutional distance for their IAs. We refine institutional theory with respect to host and home country institutional determinants of expatriation decisions by taking into consideration the particular features of emerging markets and their firms - separately and compared to developed markets and their firms.
Keywords: emerging markets; geographic labour mobility; institutional theory; international assignments; internationalization; labour management; location choice